ANALISIS PENERAPAN MEDIA PEMBELAJARAN BAHASA INDONESIA BERBASIS TIK DALAM MEMBANGUN BUDAYA LITERASI SISWA DI SD - Santi, Arfa Novia; Darmansyah; Fitria, Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
The aim of this research is to describe the implementation of an ICT-based literacy culture, as well as identify supporting and inhibiting factors for an ICT-based literacy culture in increasing students' interest in reading in elementary schools. This research uses a qualitative approach with data collection techniques through observation, interviews and documentation. The location of this research was carried out at SD Angkasa 2 Lanud Sultan Syahril. Research findings include: 1) Implementation of a literacy culture involving reading corners, reading 15 minutes before learning, and providing a library; 2) Implementation of an ICT-assisted literacy culture through e-libraries, projectors, learning materials using PPT and digital books that guide teachers in learning; 3) Supporting factors involve the role of schools by providing infrastructure, students' interest in reading, and good learning enthusiasm from teachers; 4) Inhibiting factors include inadequate infrastructure, conditions of students and an environment that is less supportive, students' lack of interest in reading, and lack of parental supervision. Keywords: literacy culture, ICT-based learning media, reading